Hubungan Komunikasi Terapeutik Perawat Dengan Kepuasan Pasien - Anita Putri Wijayanti; Febiana, Ceria (JURNAL TERAS KESEHATAN, 2024)
The community still uses clinics and health centers for inpatient medical care. The degree of discontent with therapeutic communication services in both public and private hospitals. The purpose of this study was to ascertain if patients levels of satisfaction in the inpatient room were correlated with nurses therapeutic communication. Chi square is the statistical test that is employed, the sample technique utilized is known as purposive sampling. A total of 42.8% of participants expressed satisfaction with the univariate analysis findings, while 57.2% expressed dissatisfaction with the outcomes. After doing bivariate analysis, it was discovered that the p value was 0.0001, signifying a substantial correlation between the therapeutic communication of nurses and the degree of pleasure that inpatients felt. Hospitals to provide monitoring or oversight regarding the application of communication. Nurses must focus more on therapeutic communication while providing patients with healthcare, with a focus on the initial stage of treatment.